Analysis Of Family Support And Diet Compliance In Hypertension Patients - Almina Rospitaria Tarigan (Universitas Islam Negeri Sumatera Utara, Medan, 2021)
Hypertension is a disease that suffered by many people in the world, including in Indonesia. Patients with hypertension must make a diet to consume foods that can increase the sufferer's blood pressure. A hypertension diet is one of the important factors in maintaining the health of hypertension sufferers to prevent disease complications. This study aimed to analysis family support, and compliance with hypertension diet in hypertensive sufferers.This study used a cross-sectional design conducted in the Hulu Village of Pancur Batu Public Health Center, Deli Serdang Regency. The sample size in this study was the entire population, namely hypertension sufferers. Sample (saturated sample), so that the total sample is 108 people. This study will conduct a Prevalent Rate (PR) analysis to see the risk of dietary adherence in hypertensive patients.This study showed family support in the category of bad as many as 85 people (78.7%), the implementation of hypertension diet in the non-compliant category as many as 76 people (70.4%) and adhered to the implementation of hypertension diet as many as 32 people (29.6%). of avoided foodstuffs (hypertension triggers) it is known that for this type of foods high in cholesterol is (a) grilled/boiled meat, which is as much as 76 people (70.4%), (b) meat or chicken skin, which is as much as 55 people (50.9%), and (c) chicken yolks, which is as many as 67 people (62.0%). The type of food high in Sodium is; chips, which is as many as 55 people (50.9%).Pancur Batu Public Health office, seeks to increase counselling about hypertension diet, namely recommended foodstuffs, restricted foodstuffs, avoided foodstuffs and carried out continuously in place and the right time. Families to increase knowledge about the primary prevention of hypertensive diseases so that they can conduct prevention independently and provide motivation (support) to hypertension sufferers to implement the hypertensive diet